On a stochastically grain-discretised model for 2D/3D temperature mapping prediction in grinding - Li, Hao Nan; Axinte, Dragos A. (Elsevier, 2017)
Excessive grinding heat might probably lead to unwanted heat damages of workpiece materials, most previous studies on grinding heat/temperature, however, assumed the wheel-workpiece contact zone as a moving band heat source, which might be not appropriate enough to capture the realistic situation in grinding. To address this, grinding temperature domain has been theoretically modeled in this paper by using a stochastically grain-discretised temperature model (SGDTM) with the consideration of grain-workpiece micro interactions (i.e. rubbing, ploughing and cutting), and the full 2D/3D temperature maps with highly-localised thermal information, even at the grain scale (i.e. with the thermal impacts induced by each individual grain), has been presented for the first time. To validate theoretical maps, a new methodological approach to capture 2D/3D temperature maps based on an array of sacrificial thermocouples have also been proposed. Experimental validation has indicated that the grinding temperature calculated by SGDTM showed a reasonable agreement with the experimental one in terms of both 1D temperature signals (i.e. the signals that are captured at a specific location within the grinding zone) and the 2D/3D temperature maps of the grinding zone, proving the feasibility and the accuracy of SGDTM. This study has also proved that, as expected, the heat fluxes are neither uniformly-distributed along the wheel width direction nor continuous along the workpiece feed direction. The proposed SGDTM and the temperature measurement technique are not only anticipated to be powerful to provide the basis for the prevention of grinding thermal damage (e.g. grinding burns, grinding annealing and rehardening), but also expected to be meaningful to enhance the existing understanding of grinding heat/temperature than using the common approach depending on the single thermocouple technique.